2005
DOI: 10.1042/bj20050226
|View full text |Cite
|
Sign up to set email alerts
|

Mn2+-adenosine nucleotide complexes in the presence of the nitrogenase iron-protein: detection of conformational rearrangements directly at the nucleotide binding site by EPR and 2D-ESEEM (two-dimensional electron spin-echo envelope modulation spectroscopy)

Abstract: Both ATP and a bivalent nucleotide-bound metal activator, normally Mg 2+ , are required for nitrogenase activity. EPR and ESEEM (electron spin-echo envelope modulation) measurements have been carried out on adenosine nucleotides in which the Mg 2+ ion that is usually bound is replaced by Mn 2+ in the presence of Kp2 (nitrogenase Fe-protein from Klebsiella pneumoniae). The Mn 2+ zero-field splitting parameters have been determined from the EPR-spectrum to be |D| = 0.0125 cm −1 with a rhombicity λ = E/D = 0.31 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…Our observation that V and Fe can be incorporated into the NifEN-associated precursor suggests the ability of Fe protein to mobilize metals other than Mo. Indeed, it was reported earlier that V and Mn can bind to the Fe protein in the presence of nucleotide [ 17 , 18 ]. Additionally, in the case of V, it has been demonstrated that V(V) (supplied in the form of VO 4 3− ) is reduced to V(IV) by the Fe protein before it can bind to the nucleotide binding site of the latter [ 17 ].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Our observation that V and Fe can be incorporated into the NifEN-associated precursor suggests the ability of Fe protein to mobilize metals other than Mo. Indeed, it was reported earlier that V and Mn can bind to the Fe protein in the presence of nucleotide [ 17 , 18 ]. Additionally, in the case of V, it has been demonstrated that V(V) (supplied in the form of VO 4 3− ) is reduced to V(IV) by the Fe protein before it can bind to the nucleotide binding site of the latter [ 17 ].…”
Section: Discussionsupporting
confidence: 55%
“…Indeed, it was reported earlier that V and Mn can bind to the Fe protein in the presence of nucleotide [17, 18]. Additionally, in the case of V, it has been demonstrated that V(V) (supplied in the form of VO 4 3− ) is reduced to V(IV) by the Fe protein before it can bind to the nucleotide binding site of the latter [17].…”
Section: Discussionmentioning
confidence: 99%
“…A similar approach to determine the number of nearby magnetic nuclei ( 1 H, 13 C, 17 O) was previously used for Gd 3+ complexes. 12,37,38 The dramatic differences in the cfi of different Gd 3+ complexes in those works have necessitated a somewhat more elaborate procedure based on obtaining the separate ENDOR spectra for the |−1/2⟩ ↔ |1/2⟩ transition of the Gd 3+ spin S = 7/2 and then normalizing these spectra by the ESE amplitude associated with this transition.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The values fall within the typical range reported for this nucleus. [27,28] The absence of combination peaks appears to indicate that these interactions result from different superoxide species localised at different surface sites (speciation). This is consistent with the two different g zz factors (2.14 and 2.091) observed in the CW-EPR spectrum.…”
Section: Experimental and Computational Detailsmentioning
confidence: 93%